2015
DOI: 10.5539/gjhs.v7n6p319
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Olfactory Function in Patients With Schizophrenia

Abstract: The aim of this study was to compare olfactory threshold, smell identification, intensity and pleasantness ratings between patients with schizophrenia and healthy controls, and (2) to evaluate correlations between ratings of olfactory probes and illness characteristics. Thirty one patients with schizophrenia and 31 control subjects were assessed with the olfactory n-butanol threshold test, the Iran smell identification test (Ir-SIT), and the suprathreshold amyl acetate odor intensity and odor pleasantness rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
(65 reference statements)
1
6
0
1
Order By: Relevance
“…By contrast, another study ( Walsh-Messinger et al, 2018 ) showed that schizophrenic men rated pleasant odors (orange, apple, mint,…) less pleasant than healthy men whereas no difference was observed between healthy and schizophrenic women. When studies related to this topic focused on gender differences in patients with schizophrenia, some of them showed that schizophrenic men rated pleasant odorants as more pleasant than schizophrenic women and healthy participants whatever the concentration level ( Moberg et al, 2003 ; Robabeh et al, 2015 ). Other studies found no gender differences in odor hedonic judgment ( Hudry et al, 2002 ; Lui et al, 2020 ).…”
Section: Sex Differences In Psychiatric Disordersmentioning
confidence: 99%
“…By contrast, another study ( Walsh-Messinger et al, 2018 ) showed that schizophrenic men rated pleasant odors (orange, apple, mint,…) less pleasant than healthy men whereas no difference was observed between healthy and schizophrenic women. When studies related to this topic focused on gender differences in patients with schizophrenia, some of them showed that schizophrenic men rated pleasant odorants as more pleasant than schizophrenic women and healthy participants whatever the concentration level ( Moberg et al, 2003 ; Robabeh et al, 2015 ). Other studies found no gender differences in odor hedonic judgment ( Hudry et al, 2002 ; Lui et al, 2020 ).…”
Section: Sex Differences In Psychiatric Disordersmentioning
confidence: 99%
“…Olfactory bulb mitral cells synapses with neuroepithelium, retrieving information throughout the olfactory tract to primary olfactory areas and other regions that play crucial roles in emotion regulation and executive planning. Olfactory functional impairment may be a biological marker of schizophrenia susceptibility [16]. Performing a meta-analysis on olfactory dysfunction in schizophrenia patients, high risk groups and first degree relatives, Moberg PJ et al revealed that both schizophrenia patients and high risk individuals had moderate degree of olfactory dysfunction and their first degree relatives had mild or moderate olfactory dysfunction [17].…”
Section: Discussionmentioning
confidence: 99%
“…There are several aspects of olfaction that can be assessed to characterize the schizophrenia-spectrum disorders (SSD). In particular, subjects affected by this neuropsychiatric disease present alterations in performing correctly diverse olfactory tasks, such as odor sensitivity, identification and discrimination, when exposed to different odorants [60,61,[189][190][191][192]. Due to the disbalance in olfactory activity, it has been suggested to consider this deficit as a parameter to identify SSD.…”
Section: Schizophrenia and Autismmentioning
confidence: 99%